AUTOMATIC DOOR LOCK OPENER FOR HOSTEL STUDENTS IN AN ATTEMPT TO IMPROVE THE SECURITY OF THEIR VALUABLES - Romzee, Adee Deax; Kotin, Haini; Sibin, Paidin; Tamrin, Miliani; Nordin, Muhamad Nur Farhan; Idek, Sirhajwan (MATTER: International Journal of Science and Technology, 2020)
The goal of this research project was to examine the effectiveness of an automatic lock which might help hostel students secure their valuables and privacy by preventing their lockers from being broken into. This lock could be unlocked through a mobile app by embedding the device with a specifically designed system consisting of Arduino Uno, Bluetooth HC-06, and servomotor. Most students who stayed at school hostels had the experience of losing their locker keys due to misplacement, recklessness, and sometimes theft. This posed an issue for them as losing the physical keys might put their lockers at the risk of being broken into by anyone and it also made it difficult for them to retrieve their belongings. Hence, this project was developed in order to help hostel students avoid this type of incident. 20 students were involved in this study. They tested the innovation and rated their feedback on it. The findings showed that the device gained approval from the students. This indicated that this device has the potential to be introduced across schools and colleges in the state.